Fatal meningococcal septicemia without meningeal signs, contribution of the peripheral smear in diagnosis: Report of a case - Deepti Mutreja; Nikhil Moorchung; S J Manasa; Jeenu Varghese (Wolters Kluwer Medknow Publications, 2018)
Acute meningococcemia is characterized by extensive purpurae consisting of both petechiae and ecchymoses. This condition can be rapidly fatal without treatment due to shock and severe consumptive coagulopathy. We report a case of fatal meningococcal septicemia in a military recruit who presented with fever and associated rapidly progressive purpuric rash (purpura fulminans) without any meningeal signs. Evaluation revealed evidence of disseminated intravascular coagulopathy and multiorgan failure. Diplococci were demonstrated in peripheral blood neutrophils and monocytes. On autopsy, extensive hemorrhages were found in both adrenals, lungs, liver, skin, and kidneys with secondary hemophagocytic lymphohistiocytosis in bone marrow. This report highlights useful information obtained from examination of peripheral blood smear in purpura fulminans.